The Relationship Between Spraying Frequency and Incidence of Anemia in Farmers - Hotman Natama Nainggolan; Fitria Saftarina; Suharmanto Suharmanto; Dyah Wulan Sumekar Rengganis Wardani; Betta Kurniawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Various types of pesticides commonly used by farmers and the public include insecticides, fungicides, and herbicides. Excessive pesticide use in agricultural settings can lead to adverse health effects, one of which is anemia. This study aimed to analyze the relationship between pesticide spraying frequency and the incidence of anemia among horticultural farmers in Gisting District, Tanggamus Regency, in 2025. A quantitative, case-control design was employed. The study was conducted in Gisting District, Tanggamus Regency, Lampung Province, from August 2024 to January 2025. The study population consisted of 41 anemic farmers with hemoglobin levels below 13 g/dL, and 41 non-anemic farmers as the control group. Purposive sampling was used, with the case group comprising anemic farmers and the control group including non-anemic respondents. The independent variable was spraying frequency, and the dependent variable was anemia. Data on spraying frequency were collected via questionnaire, while anemia was assessed through laboratory analysis. Data analysis included univariate and bivariate methods, with the Chi-Square test applied for inferential statistics. Results showed that the majority of farmers in the case group (73.2%) sprayed pesticides more than twice per week, whereas 53.7% of the control group sprayed less than twice per week. The analysis yielded a p-value of 0.024, indicating a significant association between spraying frequency and anemia incidence. The odds ratio (OR) of 3.158 (95% CI: 1.253–7.957).